Identifikasi Paparan Pediculus Humanus Capitis pada Anak Asuh di Panti Asuhan - Rianita Putri; Fitriani Kahar; Damas Triyono (Poltekkes Kemenkes Semarang, 2020)
Pediculus humanus capitis is a parasite known as head lice. This parasite causes itching that interferes with concentration, as well as irritation of the scalp. One of the factors for the spread of this parasite is personal hygiene that is low and quickly spreads in a crowded living environment. The purpose of this study was to describe the exposure to Pediculus humanus capitis in foster children at the An-Nahl Orphanage, Sragen Regency. This research method is descriptive research through cross sectional approach. The results of this study showed that 12 foster children (86%) in An-Nahl Orphanage, Sragen Regency had Pediculus humanus capitis and 2 foster children (14%) did not find Pediculus humanus capitis. Foster children at the An-Nahl Orphanage who have good personal hygiene category, 2 foster children (14%) are negatively exposed to Pediculus humanus capitis, sufficient category is 4 foster children (29%) are positively exposed to Pediculus humanus capitis, bad personal hygiene category is 8 foster children (57%) were positively exposed to Pediculus humanus capitis. The conclusion of the study was Pediculus humanus capitis was found in foster children at An-Nahl Orphanage, Sragen Regency, as many as 57% of all foster children had poor personal hygiene